Effect of Customer Relationship Management on Customer Satisfaction in SMEs Business (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the effectiveness of Customer Relationship Management (CRM) in a single F&B business that attracts a high number of first-time visitors yet struggles to convert them into repeat customers. The study aimed to analyze the relationship between CRM dimensions, customer satisfaction, and customer retention and identify the CRM dimension that shows the weakest performance. A quantitative approach was applied. Data from 100 respondents were collected through a structured Likert-scale survey measuring three CRM dimensions—Customer Knowledge Management (CKM), Customer Interaction Management (CIM), and IT-CRM—along with customer satisfaction and retention. The dataset was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect effects within the proposed model. The results show that all CRM dimensions exert a significant positive influence on customer satisfaction, with CKM emerging as the strongest predictor, followed by CIM and IT-CRM. Customer satisfaction, in turn, positively affects retention intention, confirming the mediating role of satisfaction within the CRM–retention relationship. Among the CRM dimensions, IT-CRM received the lowest performance scores, indicating that digital enablement and CRM-related technology represent the weakest capability within the firm and require priority improvement. These findings emphasize the importance of strengthening CRM dimensions—particularly CKM and IT-CRM—to enhance customer satisfaction and reinforce retention intentions. The study contributes empirical evidence to CRM research within small F&B contexts by demonstrating how different CRM components influence satisfaction-driven loyalty outcomes and by highlighting the specific capability gaps that hinder the firm’s ability to retain customers effectively.